2013
DOI: 10.1038/gim.2012.184
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from the EGAPP Working Group: can testing of tumor tissue for mutations in EGFR pathway downstream effector genes in patients with metastatic colorectal cancer improve health outcomes by guiding decisions regarding anti-EGFR therapy?

Abstract: EGAPP REcommEndAtion stAtEmEnt summary of recommendations: The Evaluation of Genomic Applications in Practice and Prevention (EGAPP) Working Group (EWG) found that, for patients with metastatic colorectal cancer (mCRC) who are being considered for treatment with cetuximab or panitumumab, there is convincing evidence to recommend clinical use of KRAS mutation analysis to determine which patients are KRAS mutation positive and therefore unlikely to benefit from these agents before initiation of therapy. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…However, despite this progress, the EGAPP (Evaluation of Genomic Applications in Practice and Prevention) Working Group (www.egappreviews.org) found only adequate evidence for an association of KRAS genotype at codons 12 and 13 with diminished treatment response to anti-EGFR therapy, but not for BRAF V600E, mutations in NRAS or PIK3CA , or loss of PTEN or AKT expression [6]. One reason for this uncertainty is the lack of genetic follow-up data in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite this progress, the EGAPP (Evaluation of Genomic Applications in Practice and Prevention) Working Group (www.egappreviews.org) found only adequate evidence for an association of KRAS genotype at codons 12 and 13 with diminished treatment response to anti-EGFR therapy, but not for BRAF V600E, mutations in NRAS or PIK3CA , or loss of PTEN or AKT expression [6]. One reason for this uncertainty is the lack of genetic follow-up data in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors than KRAS mutation status likely affect response to anti-EGFR therapy, because the response rates among patients with wild-type KRAS are less than 20% [1], [6], [7]. Recent investigations have identified genes and proteins downstream of KRAS in the mitogen-activated protein kinase signaling pathway, which affect unresponsiveness to anti-EGFR therapy, including the BRAF V600E mutation, mutations in NRAS or PIK3CA (exons 9 and 20), or loss of PTEN or AKT expression [8][10].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the Evaluation of Genomic Applications in Practice and Prevention (EGAPP) Working Group (EWG) found insufficient evidence to recommend or discourage testing for mutations in BRAF V600E, NRAS, or PIK3CA and/or loss of PTEN or AKT protein. Therefore, the EWG discourages the use of these tests for deciding whether to introduce anti-EGFR therapy with cetuximab or panitumumab until more evidence supports improved clinical outcomes [69]. Moreover, a meta-analysis suggests that mutations in KRAS exons 3 and 4, NRAS , BRAF , PIK3CA , and nonfunctional PTEN predict resistance to anti-EGFR therapies [70] and concluded that these biomarkers should be implemented for prediction of clinical benefit from anti-EGFR antibodies in mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los genes candidatos a esta clasificación se encuentran además de los estudiados en este trabajo, el estudio de la inestabilidad microsatelital, p53 y PIP3k entre los más frecuentemente señalados por los estudios publicados 39 . De esta manera, la implementación de estas determinaciones son una necesidad actual y un elemento fundamental en la elección de la terapia dirigida a los portadores de esta frecuente enfermedad tumoral.…”
Section: Discussionunclassified